2011
DOI: 10.1016/j.jmaa.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Complementation and decompositions in some weakly Lindelöf Banach spaces

Abstract: Let Γ denote an uncountable set. We consider the questions if a Banach space X of the form C (K ) of a given class (1) has a complemented copy of c 0 (Γ ) or (2) for every c 0 (Γ ) ⊆ X has a complemented c 0 (E) for an uncountable E ⊆ Γ or (3) has a decomposition X = A ⊕ B where both A and B are nonseparable. The results concern a superclass of the class of nonmetrizable Eberlein compacts, namely K s such that C (K ) is Lindelöf in the weak topology and we restrict our attention to K s scattered of countable h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The first named author and Zieliński have shown that the question "Does this class contain a space on which every bounded linear operator is the sum of a scalar multiple of the identity and an operator with separable range?" is undecidable (see Corollary 3.3 and Theorem 4.1 of [36]). Note that this result does not apply to any space of the form C(αK A ) for an almost disjoint family A ⊆ [N] ω because these spaces are known not to be Lindelöf in their weak topology.…”
Section: Remark 45mentioning
confidence: 99%
“…The first named author and Zieliński have shown that the question "Does this class contain a space on which every bounded linear operator is the sum of a scalar multiple of the identity and an operator with separable range?" is undecidable (see Corollary 3.3 and Theorem 4.1 of [36]). Note that this result does not apply to any space of the form C(αK A ) for an almost disjoint family A ⊆ [N] ω because these spaces are known not to be Lindelöf in their weak topology.…”
Section: Remark 45mentioning
confidence: 99%
“…In order to establish Theorem 3.1, we need to enrich our terminology. Following the notation of [10], for an ordinal α ≤ ω 1 we put F 0 (α) = α = {β : β < α} and for n > 0 we let F n+1 (α) be the set of all finite sequences of elements of F n (α). Define F (α) = n∈N F n (α).…”
Section: A Compact Space From ♣mentioning
confidence: 99%
“…The following should be compared with the fact that our space K 1 or the space of [10] are 2-diverse and not weakly pcc by Proposition 3.1 and Theorem 1.7.…”
Section: The Spaces Of a Dow H Junnila And J Pelantmentioning
confidence: 99%
See 2 more Smart Citations